Annual Plan 1976-77 Draft Proposals (In 4 Volumes) Vol. II Haryana State - Planning Commission (Planning Commission, 1976)
Before enunciating the strategy for plan of action for agricultural programmes during the year 1976-77, it would be desirable to review the achievements of agricultural production during the first two years of Fifth plan , i.e. 1974-75 and 1975-76 vis-a-vis the targets laid by the Planning Commission for different years of the Fifth Five Year Plan.
Planning Department, Haryana Government